The Resistive Index Is a Marker of Renal Function, Pathology, Prognosis, and Responsiveness to Steroid Therapy in Chronic Kidney Disease Patients - Kikuno Hanamura; Akihiro Tojo; Satoshi Kinugasa; Kensuke Asaba; Toshiro Fujita (International Journal of Nephrology)
To evaluate the significance of the renal resistive index (RI) as a noninvasive marker of renal histological damage and a prognostic indicator, we examined RI by Doppler ultrasonography in 202 chronic kidney disease (CKD) patients who underwent renal biopsy. RI increased as the CKD stage progressed and correlated with age, systolic blood pressure, estimated glomerular filtration rate (eGFR), and renal histological changes, including glomerulosclerosis, arteriolosclerosis, and tubulointerstitial damage. Prognostic evaluation with a median follow-up period of 38.5 months revealed that patients with RI≥0.7 (high RI group, n=39) had significantly poorer renal survival than those with RI<0.65 (normal RI group, n=120) and 0.65≤RI<0.7 (high-normal RI group, n=43). The patients in the high-normal RI group showed good response to steroids. However, in the high RI group, steroid therapy did not significantly improve renal survival. Of the clinical indices studied, RI≥0.7, hypertension, proteinuria, and low eGFR at diagnosis were independent risk factors for worsening renal dysfunction. In conclusion, RI in CKD patients was considered as a marker of renal function, histological damage, and renal prognosis, and a possible determinant of indication for steroids.